2016
DOI: 10.1158/0008-5472.can-15-0906
|View full text |Cite
|
Sign up to set email alerts
|

JARID1D Is a Suppressor and Prognostic Marker of Prostate Cancer Invasion and Metastasis

Abstract: Entire or partial deletions of the male-specific Y chromosome are associated with tumorigenesis, but whether any male-specific genes located on this chromosome play a tumor-suppressive role is unknown. Here, we report that the histone H3 lysine 4 (H3K4) demethylase JARID1D (also called KDM5D and SMCY), a male-specific protein, represses gene expression programs associated with cell invasiveness and suppresses the invasion of prostate cancer cells in vitro and in vivo. We found that JARID1D specifically repress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 52 publications
1
88
1
Order By: Relevance
“…Because the cell migration assay measures only the migratory abilities of cells, we additionally examined the invasive abilities of cells using cell invasion assay in which cells digest and invade a Matrigel matrix that mimics the in vivo extracellular matrix. Similar to JARID1D knockdown ( Figures S1C and S1D ) (Li et al, 2016), ZMYND8 knockdown increased the invasiveness of DU145 and CWR22Rv1 cells ( Figures 3D, S1E, and S1F ).…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Because the cell migration assay measures only the migratory abilities of cells, we additionally examined the invasive abilities of cells using cell invasion assay in which cells digest and invade a Matrigel matrix that mimics the in vivo extracellular matrix. Similar to JARID1D knockdown ( Figures S1C and S1D ) (Li et al, 2016), ZMYND8 knockdown increased the invasiveness of DU145 and CWR22Rv1 cells ( Figures 3D, S1E, and S1F ).…”
Section: Resultsmentioning
confidence: 57%
“…Because our recent study has showed that JARID1D is an anti-invasive factor that acts against prostate cancer metastasis (Li et al, 2016), we determined whether ZMYND8 regulates cellular invasion using two androgen-independent and moderately invasive human prostate cancer cell lines DU145 and CWR22Rv1 (Nemeth et al, 1999; Sramkoski et al, 1999). ZMYND8 depletion using two independent shRNAs had a negligible effect on cell proliferation and migration abilities ( Figures 3A–3C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KDM5D has been reported to have a tumor suppressor function in prostate cancer (23). Specifically, KDM5D regulates invasion-associated genes (such as the MMP family), demethylating their H3K4me3 marks, and loss of KDM5D causes the cell to acquire invasiveness with increased H3K4me3 levels in the promoter regions of relevant genes, leading to the development of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…JARID1B can also negatively regulate the malignant state mediated by genome-wide H3K4me3 hyper-methylation present in leukemias driven by the MLL methyltransferase [21]. Recently, JARID1D was shown to be a tumor suppressor based on its downregulation, mutation, or loss in prostate cancer [22] and CCRCC [23]. In hormone-sensitive prostate cancers, JARID1D directly interacts with the androgen receptor (AR) to attenuate the transcriptional activation of AR target genes.…”
Section: Jarid1 Proteins In Cancermentioning
confidence: 99%